Oil-based rock debris foamed ceramic and preparation method thereof
By combining oil-bed rock chips, spodumene flotation tailings and desulfurization waste residue, foam ceramics are prepared by using temperature foaming agent and in-situ curing collaborative high-temperature foaming method, the high material consumption and insufficient performance in the prior art are solved. The problem is that efficient and environmentally friendly foam ceramic preparation is achieved, and mechanical strength and thermal conductivity are improved.
Patent Information
- Application Number
- CN202411335598.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-24
AI Technical Summary
In the prior art, the use of tailings and waste slag to prepare foam ceramics has problems such as high material consumption, high cost and insufficient performance, and the treatment of oil bedrock chips is not effective enough, resulting in waste of resources and environmental pollution.
Oil-bedded rock chips, spodumene flotation tailings and desulfurization waste residues are used as the main components, and foam ceramics with low density, high strength and low thermal conductivity are prepared by temperature foaming agent and in-situ curing synergistic high-temperature foaming method, and ammonia is used. Propyltriethoxysilane is used as a modifier, and the Isobam gel system is ball milled and foamed at high temperature, and adds curved-toothed stainless steel fibers to increase toughness and reduce thermal conductivity.
It realizes safe and harmless and efficient use of oil bedrock chips, reduces production costs, improves the mechanical strength and thermal conductivity of foam ceramics, solves the problem of inconsistent material uniformity and denseness, and has environmentally friendly and non-toxic characteristics.
Smart Images

Figure CN119176723A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmental protection and building materials, and specifically relates to a foam ceramic prepared from solid wastes such as oil-based rock cuttings, spodumene flotation tailings and desulfurization waste residues. Background Art
[0002] Foam ceramics are a kind of ceramic material that is fired at high temperature and has a large number of interconnected or closed pore structures in its body. Due to its advantages such as low density, high permeability, corrosion resistance, high temperature resistance and good thermal insulation performance, it is widely used in gas and liquid filtration, purification and separation, chemical catalytic carriers, sound absorption and shock absorption, advanced thermal insulation materials, biological implant materials, special wall materials and sensor materials. Since the raw materials of foam ceramics (clay, quartz, feldspar) are non-renewable resources, their large consumption has caused the price of foam ceramics to rise. With the growing call for green energy conservation, the research direction of foam ceramics has gradually shifted from feasibility studies on adjusting the formula of raw materials to key technology research such as strengthening material properties, reducing production costs, and saving energy and reducing consumption. Therefore, by developing a variety of solid wastes to coordinate the treatment of oil-based rock cuttings to prepare foam ceramics, the harmless, economical, simple process, large chip consumption, and high resource utilization rate of oil-based rock cuttings can be achieved, thus expanding the path of comprehensive utilization of oil-based rock cuttings. Summary of the invention
[0003] In view of the defects in the prior art of preparing foam ceramic products using tailings and waste residues, an object of the present invention is to provide an oil-based rock cuttings foam ceramic, which has oil-based rock cuttings, spodumene flotation tailings, and desulfurization waste residues as main components. It can not only solve the problem of large-scale accumulation of oil-based rock cuttings, but also turn waste into treasure. At the same time, oil-based rock cuttings can be used to obtain high-performance, high-value-added all-solid waste foam ceramics, so as to achieve safe, harmless, high-value and efficient utilization of oil-based rock cuttings.
[0004] Another object of the present invention is to provide a method for preparing lightweight foam ceramics using oil-based rock cuttings, spodumene flotation tailings, and desulfurization waste residue as main components and using a warm foaming agent, and using an in-situ curing and high-temperature foaming method to prepare a foam ceramic with low density, high strength, and low thermal conductivity. The raw materials of this method are all solid waste materials, the preparation cost is low, and the preparation process is simple.
[0005] In order to achieve the above object, the present invention comprises the following steps:
[0006] S1 Modification of foam ceramic raw material powder: The modifier and ultrapure water are stirred and mixed evenly in a certain mass ratio to form a modifier solution, and then the ceramic raw material powder and the modifier solution are mixed to obtain a modified ceramic raw material slurry.
[0007] S2 Preparation of oil-based rock cuttings foam ceramic slurry: Isobam powder and ultrapure water are mixed in a certain proportion to prepare a premixed liquid, and the premixed liquid and the modified ceramic raw material slurry obtained in S1 are placed in a ball mill and ball-milled to obtain a mixed slurry.
[0008] S3 drying, solidification and pressure molding: then the ground mixed slurry is injected into a Φ15mm mold; it is solidified at room temperature for 1h to 2h and then demolded, and then the solidified green body is placed in a pressurized mold for pressing, and the pressure is maintained at 5MPa to 10MPa for 10s to 30s, and finally the green body is placed in an oven at 105℃±5℃ for drying.
[0009] S4 sintering: The dried green body is placed in a muffle furnace in an air atmosphere for sintering. The sintering system of the roasting method is divided into two stages. The first stage is to heat the room temperature to 600℃~700℃ and keep it warm for 10min~30min. The second stage is to heat from 600℃~700℃ to 1080℃~1150℃ and keep it warm for 30min~90min. Finally, it is cooled to room temperature with the furnace.
[0010] In S1, dried spodumene flotation tailings, desulfurization waste residue, and oil-based rock chips are mixed to obtain ceramic raw material powder, and a modifier solution is added to the foamed ceramic raw material powder, and then the ceramic raw material powder and the modifier solution are mixed to achieve the purpose of modifying the raw material powder.
[0011] Specifically, in step S1, aminopropyl triethoxysilane is used as a modifier of the raw material, and the modifier and pure water are stirred and mixed in a mass ratio of 1:5 to 7 to form a modifier solution. The foam ceramic raw material powder is composed of the following mass percentage components: oil-based rock cuttings: 40% to 50%, spodumene flotation tailings: 20% to 30%, desulfurization waste residue: 20% to 30%, silicon carbide foaming agent 0.3% to 1%; lithium carbonate 2% to 6%; curved tooth stainless steel fiber 2% to 5%.
[0012] Among them, oil-based rock cuttings, spodumene flotation tailings, and desulfurization waste residues are used to provide framework elements (silicon and aluminum) for foam ceramics. Through the reasonable design of each component of the raw materials, the alkali metal elements in each raw material are promoted to melt with the framework elements. At the same time, the alkali metal elements in the raw materials and the introduction of lithium ions are used to reduce the formation temperature of the liquid phase, promote the formation of calcium feldspar and sodium feldspar, and further improve the performance of foam ceramics.
[0013] When SiC powder is used as a high-temperature foaming agent, at room temperature, after SiC reacts with O2, a dense SiO2 oxide layer will be attached to the surface of SiC, and the oxide layer will seriously hinder the reaction between O2 and the internal SiC. Because the ceramic raw materials contain a large amount of alkaline oxides, the destruction temperature of the SiO2 protective layer can be significantly reduced. At the same time, the presence of high-temperature liquid phase will also accelerate the diffusion rate of O2 in it, promoting the full reaction of SiC; in addition, the presence of liquid phase will also promote the formation and growth of bubbles of gas produced by the reaction, thereby obtaining foam ceramics with a porous structure inside.
[0014] Lithium carbonate is added to the raw materials as a flux and foaming agent. Li2CO3 is decomposed into Li2O and CO2 at high temperature. + Ions have a higher 3+ and Si 4+ Larger ionic radius, Li + Ion substitution Al 3+ and Si 4+ After that, the glass structure expands significantly, so these ions can migrate more freely, thus having a lower activation energy. Then, the addition of Li2CO3 increases the glass phase in the sample system. The glass phase at high temperature melts into liquid. The flow of the liquid phase makes the ceramic raw material particles more tightly bonded. At the same time, the presence of an appropriate amount of liquid phase in the system can also promote the formation of necks between material particles during the reaction, thereby effectively enhancing the mechanical strength of the material. In addition, the carbon dioxide decomposed by lithium carbonate at high temperature is wrapped by the molten liquid phase, further reducing the volume density of the foam ceramic.
[0015] Curved stainless steel fibers are added to the raw materials as a toughening agent and thermal conductive material for foam ceramics. Curved stainless steel fibers not only have the excellent toughness and ductility of metal materials, but are also not easily oxidized and have a long service life. The addition of stainless steel fibers can not only prevent the further expansion of matrix cracks, but also deviate from the original direction of advance, allowing the cracks to expand along the fiber-matrix interface or inside the matrix, absorbing more fracture work. Moreover, when the fiber is pulled out of the matrix by external force, the interface friction is used to absorb the fracture work and play a toughening role, further compensating for the brittleness of the ceramic material. In addition, the thermal conductivity of ultrafine stainless steel is much greater than that of ceramic-based materials. Therefore, during the sintering process, the damage to the ceramic matrix caused by temperature stress caused by temperature changes can be effectively reduced.
[0016] Furthermore, in step S2, the Isobam gel system is used to prepare foam ceramics by in-situ curing and high-temperature foaming method, and the modified raw material slurry in S1 is mixed with the premixed liquid, and the foam ceramic slurry is obtained after ball milling.
[0017] The specific Isobam solution is Isobam104 and Isobam106 powders weighed in a mass ratio of 3:2, and a premixed solution with a concentration of 20% to 40% is prepared in pure water. Then, the corundum ball, the modified ceramic raw material slurry, and the premixed solution are mixed in a mass ratio of 7:2:1 and ball milled at a speed of 150 rpm to 250 rpm for 60 min to 120 min.
[0018] The Isobam gel system is used to achieve gel curing effect through the mutual attraction or chemical reaction between the surface charge and groups of the powder and the groups on the polymer gelling agent, forming a "powder-molecular chain-powder" structure, thereby forming a three-dimensional gel network, fixing the powder in it, and realizing in-situ curing and molding, thereby obtaining a high-strength foam ceramic body. The process is simple, greatly improving the uniformity and dispersibility of the slurry, and the prepared high-quality slurry is conducive to obtaining foam ceramics with good structural uniformity and high strength. It is also environmentally friendly and non-toxic.
[0019] Furthermore, in step S3, the ground mixed slurry is injected into a Φ15 mm mold; the mold is cured at room temperature for 1h to 2h and then demolded, and then the cured green body is placed in a pressurized mold for pressing, and the pressure is maintained at 5 to 10 MPa for 10s to 30s, and finally the green body is placed in an oven at 105°C ± 5°C for drying. Curing at room temperature for 1h to 2h is for the purpose of solidifying the slurry and facilitating subsequent demoulding; placing the green body in a pressurized mold and pressurizing it at a pressure of 10 to 20MPa for 10s to 30s. During the pressurization process, as the pressure increases, the green body will change shape, slide against each other, the gaps will be filled, the contact points will gradually increase and be tightly connected to each other; due to the increase in the particle spacing, the interaction force between the colloidal molecules and the particles will increase, which will promote the densification of the green body and at the same time give the green body a certain mechanical strength, while also facilitating the increase in the interaction points inside the green body and promoting the mass transfer reaction between the particles during the subsequent calcination process; the pressed green body will then be dried at 105±5°C for 1h to 1.5h, which will facilitate the drying of the green body and improve the strength of the foam ceramic green body.
[0020] Furthermore, step S4 adopts a step-by-step calcination method. In the first stage, the pore-forming agent and other organic matter are removed by heating to 600°C~700°C at 5~20°C / min and the temperature is kept for 10min~30min to remove the pore-forming agent and other organic matter, while promoting the evaporation of crystal water and the decomposition of organic matter in the raw material; in the second stage, the pore-forming agent is heated to 1080°C~1150°C at 2~10°C / min and the temperature is kept for 30min~90min. The green body is melted, and the recombination between ions promotes the crystallization of crystals. At the same time, the gas-producing components begin to foam, providing conditions for the generation of pores in the later stage.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) The present invention proposes an oil-based rock cuttings foam ceramic and a preparation method thereof. In view of the characteristics and research status of foam ceramics, oil-based rock cuttings are used as raw materials, and some auxiliary materials are added for regulation to prepare foam ceramic materials with better performance. The comprehensive utilization of oil-based rock cuttings is the goal. It is not only the main means to reduce hazardous wastes and control environmental quality from the source, but also the main direction for my country to reduce the consumption of primary resources. It is conducive to promoting the unity of my country's economic benefits and ecological environmental benefits.
[0023] (2) The present invention proposes an oil-based rock cuttings foam ceramic and a preparation method thereof, wherein the raw materials are all solid waste materials, the solid waste utilization rate is high, and the preparation cost is low.
[0024] (3) The present invention proposes an oil-based rock cuttings foam ceramic and a preparation method thereof. In the method, the Isobam gel system is used to prepare the foam ceramic, which can effectively solve the problem of inconsistent uniformity and density inside the green body. At the same time, the material has the characteristics of low cost, non-toxicity and relatively environmental protection.
[0025] (4) The present invention proposes an oil-based rock cuttings foam ceramic and a preparation method thereof. The method utilizes pressure molding to prepare the foam ceramic. During the pressurization process of the ceramic matrix, pressure is applied so that the particles of the green body slide against each other as the pressure increases, filling the gaps and increasing the distance between the particles. This enhances the interaction between the colloidal molecules and the particles, promotes the densification of the green body, and enables the green body to have a certain mechanical strength.
[0026] (5) The present invention proposes an oil-based rock cuttings foam ceramic and a preparation method thereof. In the method, curved stainless steel fibers are used as auxiliary heat materials and toughening agents, which can not only effectively reduce the damage to the matrix caused by temperature stress, but also significantly improve the toughness of the oil-based rock cuttings foam ceramic.
[0027] (6) The present invention proposes an oil-based rock cuttings foam ceramic and a preparation method thereof, which utilizes an in-situ solidification combined with a high-temperature foaming method to prepare the foam ceramic. The preparation method is simple and the prepared foam ceramic has high strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention; in the drawings:
[0029] Figure 1 The process flow chart of oil-based rock cuttings foam ceramics;
[0030] Figure 2 is the XRD pattern of the best example;
[0031] Figure 3 This is a picture of a foam ceramic sample;
[0032] Figure 4 Figure 1. Cross-section of ceramic foam sample.
[0033] Table 1 is an illustration of the effects of various implementation examples. DETAILED DESCRIPTION
[0034] In order to better understand the present invention, the present invention is further described in detail below in conjunction with examples, but the content of the present invention is not limited to the following embodiments.
[0035] Example 1
[0036] In this example, the weight proportions of the raw materials (in dry state) are as follows: oil-based rock cuttings: 45 parts, spodumene flotation tailings: 35 parts, desulfurization waste residue: 20 parts, lithium carbonate: 2% to 6%, and curved tooth stainless steel fiber: 2% to 5%.
[0037] The specific steps are as follows:
[0038] S1 raw material modification: weigh 45 parts of oil-based rock cuttings, 35 parts of spodumene flotation tailings, 20 parts of desulfurization waste slag, 2% to 6% of lithium carbonate, and 2% to 5% of curved stainless steel fiber; use aminopropyl triethoxysilane as a modifier and modulate it with ultrapure water in a ratio of 1:7 to obtain a modifier solution, and finally mix the ceramic raw material powder and the modifier solution in a mass ratio of 1:1 to obtain a modified ceramic raw material slurry.
[0039] Preparation of S2 ceramic slurry: First, Isobam104 and Isobam106 powders are mixed with ultrapure water in a mass ratio of 3:2 to prepare a premixed liquid with a concentration of 20%. Then, corundum balls, modified ceramic raw material slurry, and premixed liquid are placed in a ball mill in a mass ratio of 7:2:1 and ball milled for 2 hours to obtain a mixed slurry.
[0040] S3 drying, solidification and pressure molding: then the ground mixed slurry is injected into a Φ15mm mold; it is solidified at room temperature for 1 to 2 hours and then demolded, and then the solidified green body is placed in a pressurized mold for pressing, and the pressure is maintained at 5 to 10 MPa for 10s to 30s, and finally the green body is placed in an oven at 105℃±5℃ for drying.
[0041] S4 debinding and sintering: Finally, the foam ceramic green body is placed in a muffle furnace, heated to 900°C at a heating rate of 5°C / min, and kept warm for 30 minutes, then heated to 1120°C at a rate of 10°C / min and kept warm for 60 minutes, and finally cooled by furnace cooling.
[0042] S5 Performance evaluation: After the sample is cooled, take out the foam ceramic product and test the compressive strength, apparent density, water absorption, thermal conductivity, pore structure and phase composition of the sample.
[0043] Referring to GB / T 5486-2008 "Test methods for inorganic rigid thermal insulation products", the compressive strength (MPa) and apparent density (g / cm 3 ), water absorption (%), porosity, pore size, thermal conductivity (W / (m·℃)) are 0.712MPa, 0.407g / cm 3 , 64.2%, 0.37mm, 120%, 0.127W / (m·℃).
[0044] Example 2
[0045] This embodiment includes the following components by weight: 45 parts of oil-based rock cuttings, 35 parts of spodumene flotation tailings, 20 parts of desulfurization waste residue, 0.5 parts of SiC powder, 2% to 6% of lithium carbonate, and 2% to 5% of curved tooth stainless steel fiber. The remaining steps are the same as those in Example 1.
[0046] According to GB / T5486-2008 "Test Methods for Inorganic Rigid Insulation Products", the compressive strength (MPa) and apparent density (g / cm 3 ), water absorption (%), porosity, pore size, thermal conductivity (W / (m·℃)) are 0.675MPa, 0.456g / cm 3 , 74.5%, 0.71mm, 130%, 0.047W / (m·℃).
[0047] Example 3
[0048] On the basis of the above embodiment, this embodiment includes the following components in parts by weight: 45 parts of oil-based rock cuttings, 35 parts of spodumene flotation tailings, 20 parts of desulfurization waste residue, 0.5 parts of SiC powder, 2% to 6% of lithium carbonate, and 2% to 5% of curved stainless steel fibers.
[0049] In step S2, corundum balls and modified ceramic raw material slurry are mixed in a mass ratio of 7:3, and placed in a ball mill for ball milling for 1 hour to obtain a mixed slurry.
[0050] The remaining steps are the same as those in Example 1.
[0051] Referring to GB / T 5486-2008 "Test methods for inorganic rigid thermal insulation products", the compressive strength (MPa) and apparent density (g / cm 3 ), water absorption (%), porosity, pore size, thermal conductivity (W / (m·℃)) are 0.619MPa, 0.451g / cm 3 , 67.3%, 0.57mm, 137%, 0.067W / (m·℃).
[0052] Example 4
[0053] Based on the above embodiment, this embodiment includes the following components in parts by weight: 60 parts of oil-based rock cuttings, 20 parts of spodumene flotation tailings, 20 parts of desulfurization waste residue, 0.5 parts of SiC powder, 2% to 6% of lithium carbonate, and 2% to 5% of curved stainless steel fibers.
[0054] In step S1, 60 parts of oil-based rock cuttings, 20 parts of spodumene flotation tailings, 20 parts of desulfurization waste slag, 0.5 parts of SiC powder, 2% to 6% of lithium carbonate, and 2% to 5% of curved stainless steel fiber are weighed; aminopropyl triethoxysilane is used as a modifier and is modulated with ultrapure water in a ratio of 1:7 to obtain a modifier solution, and finally the ceramic raw material powder and the modifier solution are mixed in a mass ratio of 1:1 to obtain a modified ceramic raw material slurry.
[0055] The remaining steps are the same as those in Example 1.
[0056] Referring to GB / T 5486-2008 "Test methods for inorganic rigid thermal insulation products", the compressive strength (MPa) and apparent density (g / cm 3 ), water absorption (%), porosity, pore size, thermal conductivity (W / (m·℃)) are 0.871MPa, 0.683g / cm 3 , 66.1%, 0.48mm, 124%, 0.173W / (m·℃).
[0057] Example 5
[0058] On the basis of the above embodiment, this embodiment includes the following components in parts by weight: 45 parts of oil-based rock cuttings, 35 parts of spodumene flotation tailings, 20 parts of desulfurization waste residue, 0.5 parts of SiC powder, 2% to 6% of lithium carbonate, and 2% to 5% of curved tooth stainless steel fibers.
[0059] The specific steps are as follows:
[0060] In step S1, 45 parts of oil-based rock cuttings, 35 parts of spodumene flotation tailings, 20 parts of desulfurization waste residue, 0.5 parts of SiC powder, 2% to 6% of lithium carbonate, and 2% to 5% of curved tooth stainless steel fiber are mixed, and the ceramic raw material powder obtained by the mixture is mixed with pure water in a mass ratio of 1:1 to obtain ceramic raw material powder.
[0061] The remaining steps are the same as those in Example 1.
[0062] Referring to GB / T 5486-2008 "Test methods for inorganic rigid thermal insulation products", the compressive strength (MPa) and apparent density (g / cm 3 ), water absorption (%), porosity, pore size, thermal conductivity (W / (m·℃)) are 0.772MPa, 0.604g / cm 3 , 72.9%, 0.63mm, 144%, 0.121W / (m·℃).
[0063] Example 6
[0064] On the basis of the above embodiment, this embodiment includes the following components in parts by weight: 40 parts of oil-based rock cuttings, 30 parts of spodumene flotation tailings, 30 parts of desulfurization waste residue, 0.5 parts of SiC powder, 2% to 6% of lithium carbonate, and 2% to 5% of curved stainless steel fibers.
[0065] In step S1, 40 parts of oil-based rock cuttings, 30 parts of spodumene flotation tailings, 30 parts of desulfurization waste residue, and 0.5 parts of SiC powder are mixed, aminopropyl triethoxysilane is used as a modifier, and ultrapure water is modulated at a ratio of 1:7 to obtain a modifier solution, and finally the ceramic raw material powder and the modifier solution are mixed at a mass ratio of 1:1 to obtain a modified ceramic raw material slurry. The remaining steps are the same as in Example 1.
[0066] Referring to GB / T 5486-2008 "Test methods for inorganic rigid thermal insulation products", the compressive strength (MPa) and apparent density (g / cm 3 ), water absorption (%), porosity, pore size, thermal conductivity (W / (m·℃)) are 0.779MPa, 0.378g / cm 3 , 61.7%, 0.46mm, 139%, 0.051W / (m·℃).
[0067] Example 7
[0068] On the basis of the above embodiment, this embodiment includes the following components in parts by weight: 50 parts of oil-based rock cuttings, 20 parts of spodumene flotation tailings, 30 parts of desulfurization waste residue, 0.5 parts of SiC powder, 2% to 6% of lithium carbonate, and 2% to 5% of curved tooth stainless steel fiber.
[0069] In step S1, 50 parts of oil-based rock cuttings, 20 parts of spodumene flotation tailings, 30 parts of desulfurization waste residue, 0.5 parts of SiC powder, 2% to 6% of lithium carbonate, and 2% to 5% of curved stainless steel fiber are mixed, aminopropyl triethoxysilane is used as a modifier, and ultrapure water is modulated at a ratio of 1:7 to obtain a modifier solution, and finally the ceramic raw material powder and the modifier solution are mixed at a mass ratio of 1:1 to obtain a modified ceramic raw material slurry. The remaining steps are the same as in Example 1.
[0070] Referring to GB / T 5486-2008 "Test methods for inorganic rigid thermal insulation products", the compressive strength (MPa) and apparent density (g / cm 3 ), water absorption (%), porosity, pore size, thermal conductivity (W / (m·℃)) are 0.648MPa, 0.253g / cm 3 , 77.4%, 0.54mm, 141%, 0.059W / (m·℃).
[0071] Table 1 Effect table of each example
[0072]
[0073] It can be seen from Table 1 that the preparation methods of Example 2, Example 6 and Example 7 are all within the protection scope of the present invention, and their compressive strength is between 0.5 MPa and 0.8 MPa; the apparent density is 0.15 g / cm 3 ~0.30g / cm 3 ; Porosity: 60-80%, pore size: 0.2-0.8 mm, water absorption: 100%-150%, thermal conductivity: 0.045W / (m·℃)-0.060W / (m·℃);
[0074] Compared with Example 2, Example 1 has the same components and preparation methods, but no foaming agent is used in Example 1, and SiC is used as a high-temperature foaming agent in Example 2. Since no foaming agent is added, the gas-generating component of the raw materials in Example 1 fails to achieve a foaming effect, resulting in smaller pores in the foam ceramic, larger volume density, and lower strength;
[0075] Compared with Example 2, No Isobam powder was added as the gel system, and high temperature curing was adopted. Due to the lack of Isobam powder, the green body was poorly formed, and there were problems of inconsistent internal uniformity and density in the green body, which resulted in low sample strength and high density. At the same time, high temperature curing easily caused problems such as high energy consumption and complicated preparation process.
[0076] Compared with Example 2, the ratio of raw materials in Example 4 is not within the scope of protection of the present invention. Due to the difference in the substrate components, the gas production, liquid phase viscosity, skeleton structure and crystal type of the foam ceramic vary greatly, resulting in the failure to meet the requirements of the present invention.
[0077] Compared with Example 2, Example 5 does not modify the ceramic raw material, so that during the gelation process, the gel ions cannot be evenly distributed, resulting in poor uniformity of the green body structure and the sample performance cannot meet the requirements of the present invention.
Claims
1. An oil-based rock cuttings foam ceramic and a preparation method thereof, characterized in that: S1 Modification of foam ceramic raw material powder: The modifier and ultrapure water are stirred and mixed evenly in a certain mass ratio to form a modifier solution, and then the ceramic raw material powder and the modifier solution are mixed to obtain a modified ceramic raw material slurry. S2 Preparation of oil-based rock cuttings foam ceramic slurry: Isobam powder and ultrapure water are mixed in a certain proportion to prepare a premixed liquid, and the premixed liquid and the modified ceramic raw material slurry obtained in S1 are placed in a ball mill and ball-milled to obtain a mixed slurry. S3 drying, solidification and pressure molding: then the ground mixed slurry is injected into a Φ15mm mold; it is demoulded after being solidified at room temperature for 1h to 2h, and then the green body is placed in a pressurized mold for pressing, and the pressure is maintained at 5MPa to 10MPa for 10s to 30s, and finally the green body is placed in an oven at 105℃±5℃ for drying. S4 sintering: The dried green body is placed in a muffle furnace in an air atmosphere for sintering. The sintering system of the roasting method is divided into two stages. The first stage is to heat the room temperature to 600℃~700℃ and keep it warm for 10min~30min. The second stage is to heat from 600℃~700℃ to 1080℃~1150℃ and keep it warm for 30min~90min. Finally, it is cooled to room temperature with the furnace.
2. The oil-based rock cuttings foam ceramic and the preparation method thereof according to claim 1, characterized in that: In step S1, the foam ceramic raw material powder is composed according to the following mass ratio: Oil-based cuttings: 40% to 50%; Spodumene flotation tailings: 20% to 30%; Desulfurization waste residue: 20% to 30%; Silicon carbide: 0.3% to 1%; Lithium carbonate: 2% to 6%; Curved stainless steel fiber: 2%~5%.
3. The oil-based rock cuttings foam ceramic and the preparation method thereof according to claim 1, characterized in that: In the step S1, aminopropyltriethoxysilane is used as a modifier of the raw material, and the modifier and ultrapure water are stirred and mixed evenly in a mass ratio of 1:5-7 to form a modifier solution; then the ceramic raw material powder and the modifier solution are mixed in a ratio of 1:
1.
4. The oil-based rock cuttings foam ceramic and the preparation method thereof according to claim 1, characterized in that: In the step S2, the Isobam solution is prepared by weighing Isobam104 and Isobam106 powders in a mass ratio of 1-3:1-2, and preparing a premixed solution with a concentration of 20% to 40% in pure water.
5. The oil-based rock cuttings foam ceramic and the preparation method thereof according to claim 1, characterized in that: In step S2, the corundum balls, ceramic raw material slurry, and premixed liquid are put into a ball mill at a mass ratio of 7:2:1 and ground at a speed of 200-300 rpm for 60-200 min. The firing system is as follows: in the first stage, the material is heated to 600-700°C at 5-20°C / min and kept warm for 10-30 min; in the second stage, the material is heated from 600-700°C to 1080-1150°C at 2-10 min / °C and kept warm for 30-90 min; and finally, the material is cooled to room temperature with the furnace.
6. An oil-based rock cuttings foam ceramic and a preparation method thereof, characterized in that: Obtained by the preparation method according to any one of claims 1 to 5.
7. The oil-based rock cuttings foam ceramic and the preparation method thereof according to claim 6, characterized in that: The compressive strength of the foam ceramic is 0.5MPa-0.8MPa; the apparent density is 0.15g / cm 3 ~0.30g / cm 3 ; Porosity: 60-80%, pore size: 0.2-0.8 mm, water absorption: 100%-150%, thermal conductivity: 0.045 W / (m·℃)-0.060 W / (m·℃). The foam ceramic is formed with a matrix structure mainly composed of quartz, calcium feldspar, barium feldspar, and nepheline, and also contains barite crystals.
Citation Information
Patent Citations
Method for preparing Ca-ZrO2 foam ceramic through novel gel-casting system and Ca-ZrO2 foam ceramic
CN104926357A
Ceramic tile made from desulfurized residues and glaze residues, and production method of ceramic tile
CN109796188A
Porous water-absorbing red pottery steaming block and preparation method thereof
CN110803913A
Method for preparing porous water-retaining ceramic material from spodumene flotation tailings
CN111393139A
High-porosity thin microporous composite ceramic plate and preparation method thereof
CN111410513A
